2011
DOI: 10.1186/1479-5876-9-181
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell treatment for patients with autoimmune disease by systemic infusion of culture-expanded autologous adipose tissue derived mesenchymal stem cells

Abstract: Prolonged life expectancy, life style and environmental changes have caused a changing disease pattern in developed countries towards an increase of degenerative and autoimmune diseases. Stem cells have become a promising tool for their treatment by promoting tissue repair and protection from immune-attack associated damage. Patient-derived autologous stem cells present a safe option for this treatment since these will not induce immune rejection and thus multiple treatments are possible without any risk for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
95
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(100 citation statements)
references
References 111 publications
0
95
0
5
Order By: Relevance
“…The third patient received 4 times iv injection of 200 Â 10 6 AdMSC in intervals of one month. All 3 patients improved and no adverse events were observed [100].…”
Section: Clinical Experience With Msc In Patients With Rheumatoid Artmentioning
confidence: 96%
See 1 more Smart Citation
“…The third patient received 4 times iv injection of 200 Â 10 6 AdMSC in intervals of one month. All 3 patients improved and no adverse events were observed [100].…”
Section: Clinical Experience With Msc In Patients With Rheumatoid Artmentioning
confidence: 96%
“…A fourth small study describes 3 RA patients who received adipose tissue derived MSC (AdMSC) [100]. Five grams of fat tissue were collected by liposuction, transferred immediately to the GMP facility and Stromal Cell Research Center of RNL BIO and culture-expanded for 3 passages using the standard protocol to obtain AdMSC.…”
Section: Clinical Experience With Msc In Patients With Rheumatoid Artmentioning
confidence: 99%
“…A controlled prospective trial was recommended by the authors. A single case report of a 35-year-old female showed significantly improved strength after 4 IVI injections of autologous expanded adipose derived MSC at three months follow-up [35].…”
Section: Dermatomyositis/polymyositis (Dm/pm)mentioning
confidence: 99%
“…Clinical benefit was seen in all cases without significant toxicity. All patients received multiple injections of MSC, in two cases IVI and a third, intra-articular [35].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…In RA patients, the studies performed to evaluate the efficacy and biologic activity of MSC have shown some benefit, In the first study, intra-articular injections of cells to patients with RA improved the symptoms dramatically [58]. In another study [59], of four subjects with refractory rheumatoid arthritis transplanted with MSC, three experienced a reduction in ESR, DAS-28 (28-joint disease activity score) and pain VAS score at 1 and 6 months after transplantation.…”
Section: Rheumatoid Arthritismentioning
confidence: 98%